Gastropod assemblage structure in response to microlocation stressors in Tanjung Bunga, Bangka Island, Indonesia - Arizona, Mohammad Oka; Batubara, Geothani Harapan putera; Rema, Dareen Nadya; Pradita, Giandi Dharma (Journal of Marine Resources and Coastal Management, 2026)
Gastropods are an important component of mangrove ecosystems, contributing to the maintenance of ecological functions; however, their presence is highly vulnerable to anthropogenic activities. This study aimed to analyze the community structure of gastropods in response to microlocation-specific stressors in Tanjung Bunga, Bangka Island, Indonesia. Observations were conducted at three stations within a single site but under different environmental pressures, namely Station 1 (adjacent to mining areas), Station 2 (sewage outfall), and Station 3 (fishing activity area). Each station was sampled using three 10 × 10 m transects, with five 1 × 1 m plots per transect (15 plots per microlocation), and the data were analyzed using ecological indices. A total of 10 species from seven families were identified, showing varying distribution patterns. Station 2 exhibited the highest species richness (8 species), followed by Station 3 (7 species) and Station 1 (5 species). Four species, i.e., Batillaria minima, Littoraria scabra, Chicoreus capunicus, and Cerithidea quadrata, were recorded across all stations, indicating high tolerance to multiple stressors. In contrast, Ellobium aurisjidae and Nerita petiti were restricted to Station 2, while Monodonta labio and Nerita undata were found only at Station 3. Ecological index analysis revealed that the mining site had the lowest diversity (H′ = 1.034) and species richness (R = 1.369), whereas Station 2 recorded the highest richness (R = 1.979). Water quality across all stations was relatively similar, with pH 6, temperature ranging between 27–28 °C, salinity 28–30 ppt, and sandy mud substrates. These findings suggest that, although water quality remained stable, variations in anthropogenic stressors significantly influenced gastropod community structure.